The Impact of Regulating Inadequate Local Tax Types on Fiscal Independence - Muja'hidah, Muja'hidah; Syamsuddin, Adiesty S. P. (Universitas Lampung, 2023)
This study examines the impact of regional autonomy on fiscal independence, particularly through the ability of local governments to generate revenue without reliance on the central government. Effective governance requires a sustainable budget, and Law Number 1 of 2022 on Financial Relations Between the Central and Local Governments grants local governments the authority to impose taxes. However, the law restricts local governments to collecting only specified types of taxes, which must be established through local regulations (*Perda*), and prohibits the introduction of new tax types. The selection of tax types is contingent upon the existence of tax objects with sufficient potential to contribute to Locally-Generated Revenue (LGR) and enhance fiscal independence. This study aims to analyze the regulation of local tax types for autonomous regions and assess the implications of insufficient tax potential on fiscal decentralization. Utilizing a normative-juridical approach, with legislative, conceptual, and historical perspectives, the findings indicate that inadequate tax objects undermine fiscal decentralization by failing to significantly increase PAD. Consequently, a feasibility study is recommended to assess the potential of local taxes before their inclusion in regional regulations.